2019
DOI: 10.1177/0963689719836763
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation with Human Umbilical Cord Blood Stem Cells Ameliorates Ischemic Brain Injury – A Brain Transcriptome Profiling Analysis

Abstract: Our group previously demonstrated that administration of a CD34-negative fraction of human non- hematopoietic umbilical cord blood stem cells (UCBSC) 48 h after ischemic injury could reduce infarct volume by 50% as well as significantly ameliorate neurological deficits. In the present study, we explored possible mechanisms of action using next generation RNA sequencing to analyze the brain transcriptome profiles in rats with ischemic brain injury following UCBSC therapy. Two days after ischemic injury, rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…64 In addition, UC-BSCs can inhibit the immune response and decrease the size of the ischemic brain lesion. 65 These results indicate their potential in ischemic brain injury.…”
Section: Bone Marrow-derived Mscsmentioning
confidence: 78%
See 3 more Smart Citations
“…64 In addition, UC-BSCs can inhibit the immune response and decrease the size of the ischemic brain lesion. 65 These results indicate their potential in ischemic brain injury.…”
Section: Bone Marrow-derived Mscsmentioning
confidence: 78%
“…39 NSCs, BM-MSCs, AD-MSCs, or UC-BSCs IV administration has shown neuroprotection in ischemic stroke. 39,48,60,64,65,69 Despite these results, stem cells delivered by the IV route are subjected to trapping in peripheral tissues (lungs, liver, spleen, and kidneys), particularly the lungs, 70 limiting cell delivery to the brain. Additionally, pulmonary embolism complications were noted in a Korean family following IV AD-MSCs administration.…”
Section: Intravenous Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…How each of these routes impacts dosing or targeting of cells to the brain is not yet clear, even after intravenous injection, the most common route of administration. Animal studies have shown that some unidentified CB cells are present near brain lesions for short periods of time following intravenous treatment of acute stroke [53, 54] or neonatal HIE with CB-MNC [55] but the function of these cells is unclear. Some evidence suggests that CB-MNC respond to chemokines by migrating to ischemic brain regions [5658].…”
Section: Discussionmentioning
confidence: 99%